Inquadramento fitosociologico delle leccete dei dintorni di Siena - de Dominicis, Vincenzo (Giornale botanico italiano, 1973)
Abstract A phytosociological study of the Quercus ilex woods in the surroundings of Siena (Italy). Numerous stands of Quercus ilex woods around Siena have been studied phytosociologically and compared to the better known similar forests of Southern France. As a rule the Siennese Quercus ilex woods (Table 1) can not be considered to belong to the association Quercetum mediterraneo-montanum Br.-Bl. 1936 because of the absence of various significant central European and montane species, nor to Quercetum galloprovinciale because of the presence of too great a number of Quercetalia pubescenti-petraeae and Querco-Fagetea species. Only rarely communities similar to the first mentioned association have been found: i.e. on Mount Cetona at 1.800 feet and in two particularly cool and humid localities at a lower height (Table 2). Taking into account the way these woods have been managed for centuries it can be concluded that they are mixed formations of Quercetum galloprovinciale and an oakwood association belonging to the order Quercetalia pubescenti-petraeae; the exploitation techniques have caused the evergreen oak to become dominant therefore creating conditions favourable to the more thermophilous and shade loving plants characterics of Q. ilex woods and at the same time bringing about a sharp decrease in the number of the light demanding species typical of deciduous oakwoods.
Keywords: phytosociological study; Quercus ilex; Southern France